Staying active and focused? The effect of parliamentary performance on candidate renomination and promotion. (November 2019) - Yildirim, Tevfik Murat; Kocapınar, Gülnur; Ecevit, Yüksel Alper
A large body of literature has focused on potential causes and consequences of candidate nomination procedures. One of the received wisdoms in this literature is that loyalty to the party leadership in centralized systems and personal vote-earning attributes in decentralized systems rank in priority for representatives' career prospects. However, the determinants of candidate nomination in countries with centralized nomination procedures have been significantly undertheorized, due in part to the implicit assumption that party loyalty outweighs any other factor in determining career decisions. We close this gap by analyzing nomination and promotion decisions in Turkey, a closed-list PR system with highly centralized nomination procedures. We argue that representatives' parliamentary performance such as parliamentary activeness and issue concentration influence parties' nomination and promotion decisions. Utilizing original data sets of biographies of 1100 MPs who served in parliament between 2002 and 2011, and over 18, 000 parliamentary speeches and 1040 bill cosponsorships, we estimate empirical models that are explicitly derived from the underlying theoretical model and find evidence that party leaderships favour incumbents who make more speeches and who display higher issue concentration, while penalizing electorally safe incumbents who seek legislative influence through private members' bills (PMBs). Results offer important implications for the study of intraparty politics and parliamentary behaviour in general, and candidate nomination in particular.